A genomic glimpse of B chromosomes in cichlids - Martins, Cesar [UNESP]; Jehangir, Maryam [UNESP] (Springer Nature, 2021)
Background: B chromosomes (Bs) are extra karyotype elements in addition to A chromosomes and are found in all major eukaryotic taxa. Among hundreds of investigated species, cichlid fishes have emerged as an interesting group of model and have contributed to unravel the complex biology of B chromosome. Objective: We review the current state of knowledge on B chromosome investigation in cichlid fish and discuss the recent genomic advances over gene and sequences hunting on Bs and their impact on the current concept of B chromosomes. Results: The Bs of cichlids have been under the subject of classical cytogenetics and high scale DNA, RNA and epigenetics analysis and a list of B chromosome genes and functional sequences has been generated. B chromosomes of cichlids are restricted to females in some species and are enriched with genes, relics of genes, transposable elements and sequences transcribing for many significant biological functions. Diverse potentially functional sequences have been described in the B chromosome of cichlids and could influence important biological characteristics as well seems to affect transcription and epigenetic modifications of the whole genome. Conclusion: One of the most enigmatic characteristics of Bs in cichlids is their genic content related to cell cycle and chromosome structure, and their influence over sex rates. The relationship of Bs with cell cycle and sex determination looks like to be connected with the drive of the Bs during cell divisions.
Keywords: Evolution; Genes; Genome; Supernumerary chromosomes